A Review on Anti Counterfeit Packaging and Use of ICT Tools to Combat the Issue of Counterfeiting - M, Soumya (International Journal of Pharmaceutical & Biological Archive, 2012)
A Review on Anti Counterfeit Packaging and Use of ICT Tools to Combat the Issue of Counterfeiting